Research on BIM Technology in the Teaching of Construction Technology Course - Liang, Jiale (Journal of Theory and Practice of Contemporary Education, 2023)
The teaching content of the construction technology course is a teaching process involving the combination of theory and practice. In the teaching process, not only the practical significance of the theoretical content should be reflected, so that the theoretical content can withstand the test of practice, but also the comprehensive content should be described and analyzed from all aspects and angles, showing the important significance of the construction technology course, To lay a solid learning foundation for students' future development in the field of architecture. This paper analyzes the research of BIM technology in the teaching of construction technology course. BIM technology can simulate the construction process, which is conducive to making abstract knowledge more concrete and easier for students to understand.